Regulation of Villin by Wnt5a/Ror2 Signaling in Human Intestinal Cells - Cheung, Rebecca; Kelly, Jacqueline; Macleod, R. John (Frontiers in Physiology, 2011)
Regulation of expression of the intestinal epithelial actin-binding protein, villin, is poorly understood. The aim of this study was to determine whether Wnt5a stimulates Ror2 in intestinal epithelia caused transient increases in phospho-ERK1/2 (pERK1/2) and subsequently increased expression of villin transcript and protein. To demonstrate Wnt5a-Ror2 regulation of villin expression, we overexpressed wild-type, truncated, or mutant Ror2 constructs in HT-29 adenocarcinoma cells and nontransformed fetally-derived human intestinal epithelial cells, added conditioned media containing Wnt5a and measured changes in ERK1/2 phosphorylation, villin amplicons and protein expression by RT-PCR and Western blot techniques. Wnt5a addition caused a transient increase in pERK1/2, which was maximal at 10 min but extinguished by 30 min. Transient transfection with a siRNA duplex against Ror2 diminished Ror2 amplicons and protein and reduced the extent of pERK1/2 activation. Structure-function analysis revealed that the deletion of the cysteine-rich, kringle, or tyrosine kinase domain or substitution mutations of tyrosine residues in the intracellular Ser/Thr-1 region of Ror2 prevented the Wnt5a-stimulation of pERK1/2. Deletion of the intracellular proline and serine/threonine rich regions of Ror2 had no effect on Wnt5a-stimulation of pERK1/2. The increase in villin expression was blocked by pharmacological inhibition of MEK1 and casein kinase 1, but not by PKC and p38 inhibitors. Neither Wnt3a nor EGF addition caused increases in villin protein. Our findings suggest that Wnt5a/ Ror2 signaling can regulate villin expression in the intestine.